Hubungan Pemakaian Alat Pelindung Diri dengan Tingkat Kecacatan Klien Kusta di Wilayah Kerja Puskesmas Jenggawah dan Tempurejo Kabupaten Jember Tahun 2014 (The Correlation of Application Universal Precaution for Prevent Degree of Disability Clients Lepro - Edho Choyrul Huzzein; Iis Rahmawati; Tantut Susanto (Pustaka Kesehatan, 2015)
Leprosy is chronic disease that caused by germs Mycobacterium leprae and could be caused problems relating to physical health that associated with a disability. Clients leprosy with disability can prevent with wearing universal precaution. The research done by observational analytic design. Design of collecting data was the level of disability and questionnare of users universal precaution. The respondent was only undergo treatment of MDT in the workplace of Jenggawah Health Centers and Tempurejo Health Centers who are 17 client leprosy. Based on research conducted that clients leprosy (35.3%) wear universal precaution and the clients leprosy (64.7%) not wear of universal precaution.Data analyzed with the technique of chi square correction. The result of a correction Fisher’s Exact test p value 0.010 show there was the relation of universal precaution with the level of disability clients leprosy. The results of research is expected to be the basis of promotion programs, prevention, and the aggrandizement of leprosy in Indonesia by integrating model intervention nursing of community and involving the related agencies. Keywords: Universal precaution, degree of disability, leprosy